Evaluation of production cross-sections for 186 Re theranostic radionuclide via charged-particle induced reactions on Tungsten - Ali, Samer K.I.; Khandaker, Mayeen Uddin; Kassim, Hasan Abu (Elsevier, 2018)
186Re (T1/2 = 89.24 h, E(β−)mean= 346.7 keV, I(β−)total=92.59%), an intense beta-emitter shows great potential to be used as an active material in therapeutic radiopharmaceuticals due to its suitable physico-chemical properties. 186Re can be produced in several ways, however charged-particle induced reactions show to be promising towards no carrier added production. In this work, production cross-sections of 186Re were evaluated following the light-charged particle induced reactions on tungsten. An effective evaluation technique such as Simultaneous Evaluation on KALMAN code combined with least squares concept was used to obtain the evaluated data together with covariances. Knowledge of the underlying uncertainties in evaluated nuclear data, i.e., covariances are useful to improve the accuracy of nuclear data.